Investigation of the mechanical properties of Al-Al2O3-Gr hybrid composite fabricated by powder metallurgy - Lee, Kelvin Khai Meng (2017)
The development of Hybrid Metal Matrix Composite (Hybrid MMC) has created a new revolution for related material's research. This makes the MMCs plays significant role in structural application such as brake disc of automobiles. Among different types of MMCs, Al based MMCs have extensive mechanical strength and fatigue properties as they can combine different properties. In this project, the Hybrid MMC, Al-Al203-Gr has better mechanical properties as compared to their base Al. The application of break disc requires material which has good performance in mechanical strength and wear properties. A singly monolithic material could not provide all the necessary properties for a particular application. The Hybrid MMC made with Al203 and Gr able to provide higher strength and wear resistance properties. Al203 increase the strength of composite and Gr increase the wear resistance as Gr is considered a solid lubricant. In addition, the homogeneity of the particles in the composite are an important criteria to ensure the properties of the MMC. In this research, Al-Al203-Gr Hybrid MMC was fabricated by powder metallurgy method because this method are consider of producing a more uniform distributed structure between the particles in the composite as compare to other manufacturing processes. Hence, there are three main objectives in this research, to fabricate the Al-Al203-Gr hybrid MMC using powder metallurgy, to investigate the mechanical properties of Al-Al203-Gr hybrid MMC and to optimize the mechanical properties of Al-Al203-Gr hybrid MMC to use this material in the structural application. In powder metallurgy method, first the AI, Al203 and Gr powders are first mixed evenly before carry on with compaction. Secondly, compaction process is performed using the hot pressing machine which then produce the green compact and the temperature were fixed at 150°C for 1.5 minutes. The green compact are then, sintered for 4 hours at 600°C with heating rate of 5°C/min. Finally, grinding and polishing has been performed to enhance the specimen surface. Simultaneously, the density, hardness test, and tensile test were carried out. Finally, the microstructure of each specimens were also observed under the metallurgical microscope. Hence, in this research, it is found that the density of the hybrid MMC specimens after the sintering process is decreased compared to the theoretical density due to the increase of porosity. The hybrid MMC showed higher hardness value as compared to other two materials. The Gr is a very hard element. Therefore, addition of Gr significantly increased the hardness of the hybrid composite.